Research on exponential chaotic synchronization for fractional-order power systems subject to time delays - Qian, Yongliang; Tang, Mingshu; Guo, Cheng; Feng, Yue; Yu, Zhongming (Journal of the Franklin Institute, 2025)
This paper deals with issue of chaotic synchronization of fractional-order delayed power (FODP) systems. Firstly, model of error dynamics for the FODP system is built. Secondly, by means of fractional calculus theory and Lyapunov functional technique, corresponding exponential synchronization criteria are derived. New Lyapunov functional is constructed so as to decrease the conservatism of the criteria. Besides, the developed relevant results are further extended to common fractional-order delayed systems. Thirdly, in order to achieve exponential chaos synchronization of the FODP systems, a fractional-order sliding mode synchronization controller using partial states of the system is also designed. Compared with the relevant control methods, the proposed control method can not only realize the rapid chaotic synchronization of the FODP system, but also save the control cost and improve the robustness of the system. Finally, validity of the obtained results is verified by bringing real data into the simulation. Effects of the time delay and the order on dynamic behavior, stability and chaotic synchronization of the power system are analyzed. Through simulation and comparison, it indicates that both of them have important effects on the dynamic behavior, the stability and the chaotic synchronization for the FODP system, and the proposed control method is effective and superior.